2010
DOI: 10.1111/j.1469-7610.2010.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of dyslexia in Chinese children: familial history of dyslexia, language delay, and cognitive profiles

Abstract: Both early language delay and familial risk strongly overlap with subsequent dyslexia in Chinese children. Overall, rapid automatized naming and morphological awareness are relatively strong correlates of developmental dyslexia in Chinese; visual skill and phonological awareness may also be uniquely associated with subsequent literacy development in at-risk and typically developing children, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 16 publications
6
63
0
Order By: Relevance
“…This interconnected growth may reflect a unified process of visual memory that is reflected both in recognition memory and in detailed form recall (copying from memory). Studies of native Chinese speakers have previously indicated such a link between handwriting skill and reading acquisition McBride-Chang et al, 2011). For example, McBride-Chang et al (2011) found that skill in handwriting across orthographies is associated with the development of Chinese literacy.…”
Section: Writing Quality Reflects Acquisition Of Orthographic Represementioning
confidence: 99%
See 2 more Smart Citations
“…This interconnected growth may reflect a unified process of visual memory that is reflected both in recognition memory and in detailed form recall (copying from memory). Studies of native Chinese speakers have previously indicated such a link between handwriting skill and reading acquisition McBride-Chang et al, 2011). For example, McBride-Chang et al (2011) found that skill in handwriting across orthographies is associated with the development of Chinese literacy.…”
Section: Writing Quality Reflects Acquisition Of Orthographic Represementioning
confidence: 99%
“…Studies of native Chinese speakers have previously indicated such a link between handwriting skill and reading acquisition McBride-Chang et al, 2011). For example, McBride-Chang et al (2011) found that skill in handwriting across orthographies is associated with the development of Chinese literacy. Specifically, they found that skill in writing Hebrew, Korean, and Vietnamese graphs from memory explained 6 % of variance in word reading for children learning to read Chinese.…”
Section: Writing Quality Reflects Acquisition Of Orthographic Represementioning
confidence: 99%
See 1 more Smart Citation
“…Consensus is also lacking as to what measure of reading is influenced by rapid naming, at what age, and with what type of language. Some studies find that rapid naming influences only measures of speed, at early ages, and more strongly in nontransparent languages, while others also find a relationship with reading accuracy, at a later age and in transparent languages [23,25,26,40,46,[48][49][50][51].…”
Section: Rapid Automatic Namingmentioning
confidence: 99%
“…Children with dyslexia have been found to be slower in naming high-frequency visual stimuli than children without dyslexia [45][46][47]. In Ref.…”
Section: Rapid Automatic Namingmentioning
confidence: 99%